Inoculation response of mycorrhizas on morphology and physiological behaviour of trifoliate orange (Poncirus trifoliata) roots under salt stress - WANG, PENG; SRIVASTAVA, A K; ZHANG, YI-CAN; U, QIANG-SHENG W (The Indian Journal of Agricultural Sciences, 2016)
Citrus is highly sensitive to salt stress, and little efforts have been successful microbiologically to mitigate such abiotic stress. In this background, trifoliate orange [Poncirus trifoliata (L.) Raf.] seedlings were inoculated with Diversispora versiformis and exposed to 100 mM NaCl treatment for 85 days under controlled conditions. The NaCl application, though, strongly inhibited root mycorrhizal colonization in seedlings, but mycorrhizal inoculation considerably increased the root projected area and number of second- and third-order lateral roots under 100 mM NaCl treatment. Mycorrhizal-inoculated seedlings showed significantly higher soluble protein concentration, ornithine decarboxylase, arginine decarboxylase, and superoxide dismutase activity in leaves and roots, irrespective of NaCl concentration. While mycorrhizal seedlings displayed significantly lower polyamine oxidase activity and diamine oxidase activity in leaves and roots, irrespective of NaCl concentration. These results, thus, suggested that mycorrhizal plants were physiologically activated through mycorrhizal inoculation to downplay the adverse effect of salt stress.